Pemberdayaan Masyarakat Program Keluarga Harapan (PKH) Terhadap Pengentasan Kemiskinan Dalam Perspektif Maqashid Syariah - Indah Sari; Hilda Hilda; Fakhrina Fakhrina (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study analyzes how PKH Community Empowerment Against Poverty Alleviation According to the Perspective of Islamic Economics in Sukadana Village, Kayu Agung District. Implementation of this research for 6 (six) months including designing, implementing and reporting research results. This study uses a qualitative research method with a descriptive approach in which data is expressed in the form of words, sentences, pictures and cannot be expressed in numbers, describing and conducting an analysis of PKH community empowerment on poverty alleviation in the Sukadana Kayu Agung Village. A total of 185 PKH recipients were used as the population with a sample of 65 PKH recipients. The data obtained from this study were sourced from the answers given by each respondent during the interview. The analysis model used is data reduction, data presentation and conclusion. In accordance with the results of the analysis, it turns out that PKH Community Empowerment in Sukadana Village, Kayuagung District is able to alleviate the poverty of PKH beneficiaries. In maqashid sharia, the provision of PKH assistance in Sukadana Kayu Agung Village can realize the benefit of PKH recipients by guaranteeing basic needs (Dharuriyat), secondary needs (Hajiyat), and complementary needs (Tahsiniyat). PKH beneficiaries are not determined by the PKH companion. PKH Facilitators serve as program implementers, receive processed data from the central government to follow up on and verify data, components and conditions for residents as PKH beneficiaries. Proposals to be included in the Integrated Social Welfare Data (DTKS) are the authority of the Regency/City regional government together with the government of the smallest scope, namely the village/kelurahan.